2000
DOI: 10.1055/s-2000-7973
|View full text |Cite
|
Sign up to set email alerts
|

Are Low Basal Serum Levels of the Thyroid Stimulating Hormone (b-TSH) a Risk Factor for Switches into States of Expansive Syndromes (Known in Germany as „Maniform Syndromes” in Bipolar I Depression?

Abstract: Switching over from depression into states known an "maniform" in Germany ("expansive syndromes") been frequently, observed and appears to be partially related to the type of antidepressive medication. Apart from the medication, some evidence suggests that additional factors such as thyroid function may be relevant for the switchover. With this background, the aim of the present study was to evaluate the hypothesis that depressed bipolar patients with lower basal TSH serum levels (b-TSH) on admission at the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…BD patients, mania or depression episode, had a reduced TSH response to thyrotropin-releasing hormone (TRH) stimulation, which may be associated with the increasing severity of symptoms in BD [52]. One previous study reported that lower basal serum TSH levels in bipolar depression patients may be a risk factor for switching over from depression into mania state [53]. What’ more, bipolar II patients showed higher TSH levels than bipolar I patients, reporting higher TSH levels in bipolar II could be considered a biological feature of differential diagnosis from bipolar I [54].…”
Section: Discussionmentioning
confidence: 99%
“…BD patients, mania or depression episode, had a reduced TSH response to thyrotropin-releasing hormone (TRH) stimulation, which may be associated with the increasing severity of symptoms in BD [52]. One previous study reported that lower basal serum TSH levels in bipolar depression patients may be a risk factor for switching over from depression into mania state [53]. What’ more, bipolar II patients showed higher TSH levels than bipolar I patients, reporting higher TSH levels in bipolar II could be considered a biological feature of differential diagnosis from bipolar I [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tricyclic antidepressant liability (23), a number of demographic and clinical risk factors have been reported in small or retrospective studies, including comorbid substance abuse (24,25), younger age (26), decreased thyroid-stimulating hormone (27), rapid cycling (10), ss genotype at the serotonin transporter (28,29), bipolar I versus II subtype (18,19,30), hyperthymic temperament (31), mixed depressive symptoms (17), past number of manic episodes (32), absence of mood stabilizer (33,34), female gender (32), and psychosis (32). With the exception of the studies by Keck et al (32) and Altshuler et al (18), these studies were single site, retrospective, or small in sample size.…”
mentioning
confidence: 99%
“…However, in a study of a mixture of patients with unipolar depression, bipolar depression, mania, and mixed manicdepressive disorder, the TSH response to the infusion of 200 μg of thyrotropin-releasing hormone was decreased in all these disorders compared with the response of patients with reactive depression, paranoid psychosis, or neurotic depression [27]. Bottlender and colleagues [28] reported that the switch rate to mania was significantly higher in a group of patients with a lower basal TSH level than in a group of patients with a higher basal TSH among those who were admitted due to bipolar depression. The antidepressant effect of thyroid hormone in the treatment of bipolar depression suggests that low thyroid function is associated with the depressive phase of BPD [29].…”
Section: Hypothalamic-pituitary-thyroid Axis/thyroid Hormonesmentioning
confidence: 96%